Evaluation of the Use of Lignocellusic Biomass in Thermal Insulation for Green Building. Issue 1 (February 2021) - Cotterill, Jacob; Ethaib, Saleem; Hashim, Khalid; Alqashou, Faisal; Al-Hayawi, Anas Y.; Abdellatif, Mawada; Gkantou, Michaela; Shubbar, Ali
Abstract: Preserving the temperature of the indoor environment within the acceptable limits during the cold weather using a minimal amount of energy consumption is an important factor in the modern housing systems and green buildings. Therefore, this study aims to provide eco-friendly insulation material (organic material). The utlised organic material in this study was Lignocellusic Biomass (it is also known as Poaceae common reed, and Phragmites australis) and straw. The insulation efficiency of this organic matter was evaluated via testing its performance under controlled conditions. The experimental work included three types of insulation, namely organic insulation (straw and reeds), industrial insulation material (fiberglass), and bricks (without insulation). The insulation level was monitored using an infrared camera. The thermal profile was created for each insulation scenario. The results showed that the efficiency of the organic insulation was similar to the fiberglass; only a 0.84% difference was noticed between the industrial and the organic insulation materials in terms of efficiency, which proves that the Lignocellusic Biomass is a potential eco-friendly alternative for the industrial insulation materials.